The Influence of Parenting and Socialization Religious Values for Early Prevention Behavior toward Lesbian, Gay, Bisexual, and Transgender - Sartika Iriany, Ieke; Pasciana, Rostiena (International Journal of Engineering and Technology, 2018)
This research motivated by the rise of deviant behavior news by various media, the deviant behavior including LGBT (Lesbian, Gay, Bisexual, and Transgender) that lately become a hot actual topic. The purpose of this study is to discuss the influence of parenting and socialization of religious values in attempt to avoid behavior prevention of lesbian, gay, bisexual, and transgender. The study used the quantitative approach with survey technique and the parents Vocational High School (SMK) Class XI in Garut Regency, West Java Province of Indonesia as its population. Seventy-two people determined through a simple random sampling. The data collection techniques used questionnaires, observations and interviews for primary data and secondary data obtained from a review of the documentation and reports from competent agencies such as the Special Services Police Garut Unit, women's and children Committee (KP2A). Data analysis performed in non-parametric statistics that would examine the influence of the independent variables: parenting and socialization of religious values, on the dependent variable: early prevention behavior LGBT. According to the research, it concluded: parenting is in the criteria fairly well. Socialization of religious values are in the criteria fairly well. Early prevention of behavior LGBT is in the criteria well. The results of the research hypothesis testing, both the main hypotheses and sub-hypotheses indicate that parenting and socialization of religious values are significant and have positive effect on early prevention LGBT behavior. The conclusion from the result of the discussion and the theories used, it found that there was an ideal democratic parenting to form the early prevention of LGBT behavior within teenagers in vocational high school. The result of the research provides input to education policy makers in order to include subjects concerning the manners of upbringing and socialization models of religious values. Particularly, to conduct affirmative movement through brochures, pamphlets about the importance of parenting. Benefits theoretically research for the development of knowledge of the parents and practically an education policy maker.Â